PERSEPSI TENAGA KESEHATAN TERHADAP PERAN APOTEKER DALAM PELAYANAN FARMASI KLINIK DI RUMAH SAKIT SARKIES ‘AISYIYAH KABUPATEN KUDUS - Ni'matul Muflihah; Ahmad Suriyadi Muslim; Gallih Kurniawan (Nusantara Hasana Journal, 2025)
Pharmacists are healthcare professionals with expertise in the field of pharmacy. Pharmacists play a role not only in drug delivery but also in clinical aspects related to therapy selection, side effect monitoring, and patient and healthcare provider education. Clinical pharmacy services are a crucial aspect in improving the quality of healthcare services in hospitals. This study aims to determine healthcare providers' perceptions of the role of pharmacists in clinical pharmacy services at Sarkies 'Aisyiyah Hospital, Kudus Regency. This study used a quantitative descriptive design with a purposive sampling technique on 90 healthcare provider respondents. The research instrument was tested for validity and reliability, with all items valid (r count > 0.361) and reliable with Cronbach's Alpha values of 0.780 and 0.789. The results showed that the majority of healthcare providers supported pharmacist involvement in medication selection (90%), side effect monitoring (93.3%), and drug interaction monitoring (91.1%). However, only 56.7% of respondents agreed with pharmacist involvement in bedside visits with patients. This indicates a limited understanding of the clinical role of pharmacists. Identified barriers included a lack of cross-professional coordination. Healthcare workers' positive perceptions of the pharmacist's role are crucial and strategic in supporting clinical pharmacy services, both for patients and the hospital environment.